8th International Symposium on High-Temperature Metallurgical Processing - Hwang, Jiann-Yang; Jiang, Tao; Kennedy, Mark William; Yücel, Onuralp; Pistorius, P. Chris; Seshadri, Varadarajan; Zhao, Baojun; Gregurek, Dean; Keskinkilic, Ender (The Minerals, Metals & Materials Series, 2017)
This collection features contributions covering the advances and developments of new high-temperature metallurgical technologies and their applications to the areas of: processing of minerals; extraction of metals; preparation of metallic, refractory, and ceramic materials; treatment and recycling of slag and wastes; conservation of energy; and environmental protection. The volume will have a broad impact on the academics and professionals serving the metallurgical industries around the world by providing them with comprehensive coverage of a wide variety of topics.